1992
DOI: 10.1021/bi00126a022
|View full text |Cite
|
Sign up to set email alerts
|

Binding of tachyplesin I to DNA revealed by footprinting analysis: significant contribution of secondary structure to DNA binding and implication for biological action

Abstract: In view of the cationic amphipathic structure of tachyplesin I and antiparallel beta-sheet as a general DNA binding motif, DNA binding of the antimicrobial peptide has been examined. Several footprinting-like techniques using DNase I protection, dimethyl sulfate protection, and bleomycin- (BLM-) induced DNA cleavage were applied in this study. Some distinct footprints with DNase I are detected, and also the sequence-specific cleavage mode of the BLM-Fe(II) complex clearly is altered in the presence of tachyple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 37 publications
4
86
0
2
Order By: Relevance
“…The nonlytic PR-39 kills bacteria by interrupting both DNA and protein synthesis (39). The DNA binding property of tachyplesin I has also been implicated in the antibiotic activity (40). The observed differences in the mechanism for bacterial killing appear to be consistent with the structural diversity among these molecules.…”
Section: Discussionmentioning
confidence: 66%
“…The nonlytic PR-39 kills bacteria by interrupting both DNA and protein synthesis (39). The DNA binding property of tachyplesin I has also been implicated in the antibiotic activity (40). The observed differences in the mechanism for bacterial killing appear to be consistent with the structural diversity among these molecules.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, AP-induced perturbation of the CM, either by defined membrane poration or diffuse membrane permeabilization, has been felt to be required and sufficient to induce eventual microbial killing (25,43,49). However, recent investigations have also implicated intracellular targets and the autolytic enzyme system as participants in AP-induced lethal pathways (36,39,44,45,51). Moreover, several recent studies have documented that the composition of the CM or CW, as well as the overall microbial surface charge of certain pathogens (e.g., S. aureus), significantly influences the net antimicrobial activity of cationic APs (26,28,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The three tandem repeats of a tetrapeptide sequence, hydrophobic amino acid-Cys-hydrophobic amino acid-Arg, within the peptide indicate that its amphipathic nature, as confirmed by nuclear magnetic resonance structural investigations (36), is probably associated with biological activity (68). In view of the amphipathic cationic structure of tachyplesin and antiparallel ␤-sheets as a general DNA-binding motif, DNA binding using footprinting analysis of the peptide was examined and indicates that tachyplesin interacts with the minor groove of DNA duplex (96). Additional studies on tachyplesin found isopeptides, tachyplesin II and tachyplesin III, and also polyphemusins I and II in hemocytes of the American horseshoe crab Limulus polyphemus and the southeast Asian horseshoe crab Tachypleus gigas (Fig.…”
Section: Arthropodamentioning
confidence: 99%